2018
DOI: 10.2478/aiht-2018-69-3106
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroxyacetone as a definitive treatment for aluminium phosphide poisoning in rats

Abstract: Aluminium phosphide (AlP), a very toxic pesticide also known as the rice tablet, releases phosphine gas upon contact with water, moisture, or gastric acid. Its mortality rate in humans is 70-100 % due to cardiogenic shock and refractory hypotension. Dihydroxyacetone (DHA) is a simple ketonic carbohydrate, mainly used for sunless skin tanning. It also plays a beneficial role in the treatment of hypotension and cardiogenic shock by restoring blood volume and cellular respiration. The aim of this study was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The median weight in our series was 70 kilograms (IQR 63-84). The medians for vital signs recorded in the ED were the following: temperature of 100.2º Fahrenheit (IQR 98.6-102.6); Clinical Practice and Cases in Emergency Medicine [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. Three (43%; 95% CI, 9-81) patients had documented fever in the ED.…”
Section: Resultsmentioning
confidence: 99%
“…The median weight in our series was 70 kilograms (IQR 63-84). The medians for vital signs recorded in the ED were the following: temperature of 100.2º Fahrenheit (IQR 98.6-102.6); Clinical Practice and Cases in Emergency Medicine [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. Three (43%; 95% CI, 9-81) patients had documented fever in the ED.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, AlP exposure did not elevate ST segment, but selegiline treatment declined ST segment at 90‐120 minutes in AlP‐treated rats (Table ). Previous reports showed that AlP‐induced elevation in ST is correlated with mortality, and lowering ST segment has good prognosis . However, a previous study on patients with Parkinson's disease showed that selegiline treatment was not concomitant with a change in QT interval, even in patients with ventricular tachycardia …”
Section: Discussionmentioning
confidence: 97%
“…Previous reports showed that AlP-induced elevation in ST is correlated with mortality, and lowering ST segment has good prognosis. 48,52 However, a previous study on patients with Parkinson's disease showed that selegiline treatment was not concomitant with a change in QT interval, even in patients with ventricular tachycardia. 53 Our results showed that AlP poisoning is associated with pathological consequences in the duodenum and stomach tissues of rats such as congestive vessels, dilation and hyperaemia in stomach, and dilated crypts and inflammatory cells in some areas of duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that dihydroxyacetone (DHA) as a simple carbohydrate can overcome hypovolemic hypotension 17 and can reduce toxicity of PH3 in HepG2 cells by increasing ATP production 7 . In another study, it has been shown that a single dose of DHA completely prevented the death caused by AlP poisoning in rats through improving blood pressure and heart rate 18 …”
Section: What Is Known and Objectivementioning
confidence: 97%
“…It has been shown that DHA normalized blood pressure and heart rate in AlP poisoning in rats 18 which might be through activation of cytochrome C oxidase, tissue oxygenation improvement and recovery of blood volume 17,37,38 . DHA reacts with nitrogen group of amino acids in corneocytes in the upper layers of the stratum corneum and is used as an ingredient in tanning products 21,39,40 .…”
Section: What Is New and Conclusionmentioning
confidence: 99%